How do supervisor-student relationship affect anxiety of graduate students? ——The mediating role of research self-efficacy and the moderating role of mindset - Li, Peng; Tang, Xiaoqing; Sun, Yongjie; Huang, Songjie (PloS one, 2025)
In China, the number of graduate students continues to increase, and graduate education is developing rapidly. However, mental health issues among graduate students are widespread. Self-efficacy and mindset have been found to moderate the effect of negative life events on individuals' anxiety and depression levels. However, few studies have extended this conclusion to postgraduate student samples. This study utilized a moderated mediation model to explore the mediating role of research self-efficacy and the moderating role of mindsets. A sample of Chinese graduate students (n = 2278) was included in the study. The results indicated that the supervisor-student relationship significantly affects the anxiety level of graduate students. Satisfaction with the supervisor-student relationship was negatively associated with anxiety. Furthermore, research self-efficacy was found to significantly mediate the impact of supervisor-student relationships on anxiety. Additionally, mindset significantly moderated the association between supervisor-student relationships and both anxiety as well as research self-efficacy. For students with a growth mindset, both their research self-efficacy and anxiety levels were less influenced by the quality of the supervisor-student relationship. These findings highlight the critical importance of healthy supervisor-student relationships for graduate students' anxiety and depression, and suggest that fostering a growth mindset can mitigate the negative effects of poor supervisor-student relationships on mental health. Therefore, efforts should be made to cultivate students' growth mindsets to enhance their mental well-being. In addition, this study extends the application of self-determination theory to the field of education by verifying the mediating role of research self-efficacy.